Analysis of Disparities in INA-CBGs Claim Verification Turnaround Time: A Case Study in Type C and B Regional Government-Owned Hospitals - Maya Kasmita; Sulaiman Putra Nagaring (CV. Get Press Indonesia, 2025)
This study investigates disparities in the Turnaround Time (TAT) for INA-CBGs claim verification between Type B and Type C Regional Public Hospitals (RSUDs) under the National Health Insurance Program (JKN). Although the regulatory TAT standard is 15 days, verification time often deviates, impacting hospital liquidity. The research quantifies the influence of Hospital Type on TAT, controlling for Case Mix Index (CMI) (Type B CMI ≈ 1.75 vs. Type C ≈ 1.25) and Pending Claim Ratio (Type C ≈ 12.5% vs. Type B ≈ 8.5%). Employing a quantitative comparative design on secondary data from 50 RSUDs (20 Type B, 30 Type C) (2021–2024), results confirm a statistically significant disparity. Type B RSUDs achieved a mean TAT of 14.2 days (near standard), significantly shorter than Type C RSUDs at 17.8 days (exceeding standard). Multivariate analysis showed that hospital type is a strong negative predictor of TAT, suggesting administrative resources and process maturity outweigh case complexity. Policy implications emphasize the need for targeted capacity-building and improving the coder-to-bed ratio in Type C RSUDs and utilizing Type B hospitals for benchmarking best practices to optimize JKN efficiency and financial sustainability.